A Signaling Pathway to Mediate the Combined Immunomodulation of Acetylcholine and Enkephalin in Oyster Crassostrea gigas - Liu, Zhaoqun; Zhou, Zhi; Wang, Lingling; Zhang, Yukun; Zong, Yanan; Zheng, Yan; Li, Meijia; Wang, Weilin; Song, Linsheng (Frontiers in Immunology, 2020)
Molluscs have evolved a primitive but complete neuroendocrine-immune (NEI) system with a vast array of neurotransmitters to conduct both humoral and cellular immunomodulation. Previous study has illustrated the immune functions of several key neurotransmitters. However, the combined effects of multiple neurotransmitters and the signaling pathway to mediate such immunomodulation have not been well understood. In the present study, iTRAQ and LC-ESI-MS/MS approaches were employed to investigate the combined immunomodulation functions of two crucial neurotransmitters, acetylcholine (ACh) and [Met5]-enkephalin (ENK), in oyster Crassostrea gigas. A total number of 5,379 proteins were identified from haemocytes of oysters after the treatments with Ach and ENK separately or simultaneously, and 1,475 of them were found to be significantly up-regulated, while 1,115 of them were significantly down-regulated. The protein expression patterns in the groups treated by ACh and ENK separately were quite similar, which were dramatically different from that in the group treated by ACh+ENK. One hundred and seventy-two proteins were found to be differentially expressed in all the three neurotransmitter-treatment groups. Functional validation proved that ACh and ENK modulated the immune response in oyster haemocytes mainly by enhancing pathogen recognition, cell apoptosis, and the enzyme activities of superoxide dismutase (SOD). Moreover, GO enrichment and co-expression network analyses demonstrated that the combined immunomodulation of ACh and ENK was basically mediated by p53, EGF-R-ErbB and Fc gamma R (FcγR) signaling pathways. These results collectively indicated that there was a combined and ordered immune regulation of multiple neurotransmitters through common signaling cascades in molluscs, which was under delicate control even without a closed regulatory system.